Prevalence and risk factors for asthma among adults in Tanzania - Hussein Hassan Mwanga; Simon Henry David Mamuya; Bente Elisabeth Moen; Cecilie Svanes (Clinical Epidemiology and Global Health)
Background: Limited information exists on the magnitude of asthma and associated factors in Africa. In Tanzania, very few studies have conducted epidemiological investigation of adult asthma. This study investigated the prevalence and risk factors for asthma in Tanzania. Methods: A cross-sectional study of 968 adults was conducted. An interviewer-administered European Community Respiratory Health Survey questionnaire was used. Current asthma was defined as having had an asthma attack, current use of asthma medication or being woken up by an attack of shortness of breath, in the past 12 months. Asthma outcomes were analysed using multivariate regression models. Results: The median age was 43 years and 50 % were females. The prevalence of current asthma was 10 %, while 4 % reported doctor-diagnosed asthma and 10 % reported ≥2 asthma symptoms. The prevalence of hay fever was 10 %, and 9 % reported family history of allergy. Risk factors associated with ≥2 asthma symptoms included hay fever (OR = 4.94; 95 %CI: 2.85–8.58), eczema (3.28; 1.51–7.11), family history of allergy (2.34; 1.23–4.47), repeated childhood chest infections (7.98; 3.70–17.24), having no food to eat (3.83; 1.86–7.87) and exposure to biomass fuels-use of wood for cooking/heating (6.52; 3.16–13.48). Nonallergic current asthma was strongly associated with low socioeconomic status (5.66; 1.16–27.71). Conclusions: Asthma was relatively common with a prevalence of 10 %. Limited food availability, exposure to biomass fuels, allergy and childhood respiratory infections, were identified as important risk factors for asthma. These findings underscore the need to identify the specific aspects of low socioeconomic status that can be targeted to reduce the asthma risk.